Case reportThe symptoms of angioedema and urticaria in the course of endocrinopathy - Bożek, Andrzej; Krajewska, Jolanta; Hadas, Ewa; Filipowska, Barbara; Jarząb, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
The study presents four cases of recurrent angioneurotic oedema and/or chronic urticaria with the concomitant following endocrine disorders: hyperthyroidism, adrenal adenoma and carcinoid. In two patients thyrotoxicosis was associated with urticaria which disappeared completely after antithyroid drug therapy. This phenomenon can be explained by the influence of antithyroid antibodies and thyroid hormones which may increase mastocyte degranulation. In another patient with adrenal adenoma, a serious angioneurotic oedema resistant to routine treatment was observed. Surgical removal of the adrenal tumour caused complete regression of all symptoms. The next patient with hormonal active intestinal carcinoid accompanied by chronic urticaria was stated. All dermatological signs receded after chemotheraphy and 131I MIBG therapy. In these two endocrinopathies biogenic amines and peptide hormones may cause urticaria.